PENGARUH KOMPETENSI DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI - Ni Putu Dewi Eka Sapitri; I Gede Aryana Mahayasa (Warmadewa Management and Business Journal (WMBJ), 2022)
BPKAD Denpasar City as a government agency is expected to give good performance considering its duties and functions related to the financial sector of the Denpasar City government. The purpose of this study was to determine the effect partially and simultaneously competence and job characteristics on employee performance at the Denpasar City BPKAD Office. The population in this study were all employees at the BPKAD office of Denpasar City as many as 98 employees, consisting of 62 non-PNS or contract employees and 36 PNS employees. Determination of the sample using saturated sampling technique, where the entire population is sampled. After the instrument test and classical assumption test were carried out, data analysis was carried out using multiple linear regression analysis, determination, t test, and F test. The results of the analysis showed that competence had a positive and significant effect on employee performance. Job characteristics have a positive and significant effect on employee performance. Competence and job characteristics simultaneously have a positive and significant effect on employee performance.